Study on the Biochemical Characterization and Selectivity of Three β-Glucosidases From Bifidobacterium adolescentis ATCC15703 - Hu, Yanbo; Zhai, Liyuan; Hong, Huili; Shi, Zenghui; Zhao, Jun; Liu, Duo (Frontiers in Microbiology, 2022)
Three β-glucosidases from Bifidobacterium adolescentis ATCC15703, named BaBgl1A, BaBgl3A, and BaBgl3B, were overexpressed in Escherichia coli. The recombinant β-glucosidases were sufficiently purified using Ni2+ affinity chromatography, and BaBgl1A exhibited the best purification efficiency with purification factor of 2.3-fold and specific activity of 71.2 U/mg. Three recombinant β-glucosidases acted on p-nitrophenyl-β-glucopyranoside (pNPβGlc) at around pH 7.0 and 30-50°C. Results of the substrate specificity assay suggested that BaBgl1A acted exclusively as a β-1,2-glucosidase, while BaBgl3A and BaBgl3B acted mostly as β-1,3-glucosidase and β-1,4-glucosidase, respectively. The substrate specificity of the three recombinant enzymes was further studied using the ginsenosides Rb1 and ginsenosides Rd as substrates. Results of thin layer chromatography (TLC) and high performance liquid chromatography (HPLC) analyses showed that BaBgl1A exhibited the highest bioconversion ability on Rb1 and Rd, where it hydrolyzed the outer C-3 glucose moieties of Rb1 and Rd into the rare ginsenosides Gypenoside XVII and ginsenoside F2 ; BaBgl3A exhibited medium bioconversion ability on Rb1, where it hydrolyzed both the outer C-3 and C-20 glucose moieties of Rb1 into the Gyp XVII and Rd; BaBgl3B was not active on Rb1 and Rd. These β-glucosidases will act as new biocatalytic tools for transforming ginsenosides and preparing active glycosides and aglycone.